Non-invasive prenatal diagnosis and screening for monogenic disorders. (October 2020) - Scotchman, E.; Shaw, J.; Paternoster, B.; Chandler, N.; Chitty, L.S.
Abstract: Cell-free fetal DNA (cffDNA) can be detected in the maternal circulation from 4 weeks gestation, and is present with cell-free maternal DNA at a level of between 5 % and 20 %. Cell-free DNA (cfDNA) can be extracted from a maternal blood sample and, although it is not possible to separate the fetal from the maternal cfDNA, it has enabled non-invasive prenatal diagnosis (NIPD) without the associated miscarriage risk that accompanies invasive testing. NIPD for monogenic diseases was first reported in 2000 and since then there have been many proof of principle studies showing how analysis of cfDNA can provide a definitive diagnosis early in pregnancy for a wide range of single gene diseases. Testing for a number of these diseases has been available in the UK National Health Service (NHS) since 2012. This review highlights the main techniques that are being used for NIPD and discusses the technical limitations of the methods, as well as the advances that are being made to overcome some of the issues. NIPD is technologically challenging for a number of reasons. Firstly, because it requires the detection of low level fetal variants in a high maternal background. For de novo and paternally-inherited variants this has been achieved through the use of techniques such as next-generation sequencing (NGS) and digital PCR to detect variants in the cffDNA that are not present in the maternal cfDNA. However, for maternally-inherited variants this is much more challenging and relies on dosage-based techniques to detect small differences in the levels of mutant and wild-type alleles. Alongside the technical advances that are making NIPD more widely available in both the public healthcare and commercial settings, it is crucial that we continue to monitor the social and ethical impact to ensure that patients are being offered safe and accurate testing.